Cerebral aspergillosis in liver transplantation. Issue 2 (February 1990) - Boon, A P; Adams, D H; Buckels, J; McMaster, P
Abstract : Nine cases of cerebral aspergillosis were identified in a series of 44 brains obtained at necropsy from patients who had undergone liver transplantation. In two of these there was dual infection with Candida albicans. The primary focus of infection was invariably in the lungs. One case of pulmonary Aspergillus infection was found with no evidence of cerebral disease. Infection tended to occur in the period soon after transplantation, was associated with high dose steroids, retransplantation, and showed a significant seasonal incidence. Neurological findings were non-specific and only two cases were diagnosed before death. Aspergillus infection soon after transplantation indicates that this organism is a considerable nosocomial hazard, particularly in the winter and spring months. Positive cultures before death are rarely obtained and antifungal treatment should be started on clinical suspicion alone.